Kinetic parameters of high jump (block) in volley-ball: case study - Grira, Y.; Abderrahman, A. B. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The purpose of this study was to investigate the relationship between the height of a vertical jump similar to a volley ball block, and isokinetic strength and flexibility of the knee flexor/extensor muscles. Moreover we quantified the effect of using or not the arms in this type of jump. Six male volleyball athletes (mean ± SD: 24 ± 0.2 years old, 82.02 ± 8.96 kg in weight, 1.82 ± 0.08 m in height) participated in this study.